2006
DOI: 10.1158/0008-5472.can-05-3087
|View full text |Cite
|
Sign up to set email alerts
|

The S100A4 Metastasis Factor Regulates Cellular Motility via a Direct Interaction with Myosin-IIA

Abstract: S100A4, a member of the Ca 2+ -dependent S100 family of proteins, is a metastasis factor that is thought to regulate the motility and invasiveness of cancer cells. Previously, we showed that S100A4 specifically binds to nonmuscle myosin-IIA and promotes the unassembled state. S100A4, thus, provides a connection between the actomyosin cytoskeleton and the regulation of cellular motility; however, the step or steps in the motility cycle that are affected by S100A4 expression have not been investigated. To examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
167
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 40 publications
(48 reference statements)
10
167
0
3
Order By: Relevance
“…Indeed, it has been shown that, in breast cancer, intracellular S100A4 can induce cell motility in part through its ability to interact with myosin-IIA and extracellular S100A4 can stimulate MMP-13 activity, possibly contributing to tumor invasion (Garrett et al, 2006;Li and Bresnick, 2006). Therefore, S100A4 can promote metastasis and crossing mice that overexpress S100A4 in the mammary epithelium with mouse models of metastasis dramatically increases the incidence of metastasis (Davies et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that, in breast cancer, intracellular S100A4 can induce cell motility in part through its ability to interact with myosin-IIA and extracellular S100A4 can stimulate MMP-13 activity, possibly contributing to tumor invasion (Garrett et al, 2006;Li and Bresnick, 2006). Therefore, S100A4 can promote metastasis and crossing mice that overexpress S100A4 in the mammary epithelium with mouse models of metastasis dramatically increases the incidence of metastasis (Davies et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Coupled to this is a myosin II-mediated contraction at the cell rear, which disconnects the cell from its ECM attachments. This mechanism requires that myosin II be rapidly transported through the dense actin network in the lamellipodium-a process facilitated by mts1, which depolymerizes myosin IIA (Li and Bresnick, 2006). By contrast, if myosin II is specifically required to squeeze a stiff nucleus through small pores, and if the brain environment prevents lamellipodium formation, then rapid redistribution of myosin II might not be required, and mts1 might be unnecessary.…”
Section: Molecular Biology Of the Cell 3364mentioning
confidence: 99%
“…Intracellular S100A4 interacts with proteins of the cytoskeleton, such as actin filaments, nonmuscle tropomyosin, and nonmuscle myosin II, thereby directly increasing cell motility. [13][14][15] S100A4 also induces a migratory phenotype by affecting cell adhesion via binding to liprin ␤1. 16 Moreover, S100A4 binds to the tumor suppressor p53 and modulates its transcriptional activity.…”
mentioning
confidence: 99%